Periodization of the training process in the preparation of highly qualified powerlifters for international competitions - Kashychkina, Oksana (Педагогічна Академія: наукові записки, 2025)
The relevance of the study is due to the need to improve approaches to periodization in the training system of high-level powerlifters, since classical models do not fully take into account the individual characteristics of athletes’ adaptation, the growing density of the international calendar and the need for prompt adjustment of training loads. It emphasizes the expediency of integrating traditional principles of periodization with modern digital methods of control and monitoring. The purpose of the article is to scientifically substantiate and systematize approaches to organizing the training process of high-level powerlifters, with a focus on increasing the effectiveness of training for international competitions. The research methodology is based on the analysis and synthesis of scientific and methodological literature, content analysis of recent publications, comparison of classical and modern periodization models, and generalization of practical experience in training high-level athletes. A systematic approach was used to establish the relationship between the volume and intensity of loads, the dynamics of recovery processes and the adaptive capabilities of the body. The study’s results showed that the multi-level organization of the training process, in the form of macro-, meso-, and microcycles, provides control over adaptation and a more accurate prediction of the athlete’s peak form. It was found that the use of digital monitoring (HRV, biomechanical analysis, and subjective fatigue indicators) increases the effectiveness of individualizing athletes’ loads. The main problems of the training process for powerlifters were identified: overload, significant individual adaptation differences, insufficient standardization of methods, and the complexity of implementing modern control technologies in practice. The scientific novelty of the study lies in the systematization of approaches to combining classical principles of periodization in the training process with innovative methods of digital control, as well as in demonstrating the effectiveness of the modular approach to building macrocycles that account for the specifics of the international competition calendar. Conclusions. The need for individualized training loads, the integration of complex recovery strategies, and digital monitoring systems to minimize the risk of overtraining and ensure the stability of sports results is proven. Prospects for further research are related to the development of personalized algorithms for planning the training process in real time, the use of artificial intelligence to predict recovery processes, as well as the study of psychophysiological aspects of powerlifters’ adaptation to the stressful conditions of international competitions.